IMPROVING THE TECHNOLOGY OF THE COGNITIVE APPROACH TO THE FORMATION OF LEXICAL COMPETENCE OF PRIMARY SCHOOL STUDENTS IN ENGLISH (Proceedings of International Educators Conference, 2024)
This article is importance of lexical skills in the context of interdisciplinary relations as an integral part of the lexical competence of a foreign language is emphasized, their specificity and conditions of formation are described.